Erysipelothrix anatis sp. nov., Erysipelothrix aquatica sp. nov. and Erysipelothrix urinaevulpis sp. nov., three novel species of the genus, and emended description of Erysipelothrix. Issue 7 (1st July 2022) - Eisenberg, Tobias; Mühldorfer, Kristin; Erhard, Marcel; Fawzy, Ahmad; Kehm, Sabine; Ewers, Christa; Semmler, Torsten; Blom, Jochen; Lipski, André; Rau, Jörg; Kämpfer, Peter; Glaeser, Stefanie P.
Abstract : Seven genotypically distinct strains assigned to the genus Erysipelothrix were isolated in different laboratories from several animal sources. Strain D17_0559-3-2-1 T and three further strains were isolated from samples of duck, pig and goose. The strains had >99 % 16S rRNA gene sequence similarity to each other and to strain VA92-K48 T and two further strains isolated from samples of medical leech and a turtle. The closest related type strains to the seven strains were those of Erysipelothrix inopinata (96.74 %) and Erysipelothrix rhusiopathiae (95.93 %). Average nucleotide identity, amino acid identity and in silico DNA–DNA hybridization results showed that the strains represented two separate novel species. One further phylogenetically distinct strain (165301687 T ) was isolated from fox urine. The strain had highest 16S rRNA gene sequence similarity to the type strains of Erysipelothrix tonsillarum (95.67 %), followed by Erysipelothrix piscisicarius (95.58 %) and Erysipelothrix larvae (94.22 %) and represented a further novel species. Chemotaxonomic and physiological data of the novel strains were assessed, but failed to unequivocally differentiate the novel species from existing members of the genus. MALDI-TOF MS data proved the discrimination of at least strain 165301687 T from all currently described species. Based on the presented phylogenomic and physiological data, we propose three novel species, Erysipelothrix anatis sp. nov. with strain D17_0559-3-2-1 T (=DSM 111258 T = CIP 111884 T =CCM 9044 T ) as type strain, Erysipelothrix aquatica sp. nov. with strain VA92-K48 T (=DSM 106012 T =LMG 30351 T =CIP 111492 T ) as type strain and Erysipelothrix urinaevulpis sp. nov. with strain 165301687 T (=DSM 106013 T = LMG 30352 T = CIP 111494 T ) as type strain.